Business development intern - Dabhade, Ruchi (ATLAS SkillTech University, 2024)
Readers Club Company is a vibrant and dedicated organization that strives to promote reading and literacy among individuals of all ages. Since its inception, the company has been driven by a mission to cultivate a lifelong love for reading and to foster intellectual curiosity within communities. The company offers a diverse range of products and services to cater to the varied interests of book enthusiasts. These include exclusive book club memberships, engaging author events and book launches, insightful reading workshops and seminars, and an online bookstore with an extensive collection of books.
Project Report on Business development intern” (2022-24) Under the Guidance of Prof. Nikita Nadkarni
Keywords: Readers Club; literacy; reading